Women’s Rights in Nepal: A Constitutional Insight (Journal of Gender and Social Issues, 2024)
The authors delve into study of constitutional protection for women in Nepal. There are several clauses in the Nepalese Constitution that promote and defend women's rights. The charter grants women a variety of rights under Article 38, including the right to procreate, the right to lineage, and the right to be free from all forms of discrimination. The constitution provides the right to proportionate participation in state apparatuses and one-third representation in the legislature in an effort to advance the cause of women. The state would undoubtedly benefit from these advancements if it wanted to establish gender-sensitive laws and policies.
Keywords: Constitution, Gender equality, Law, Nepal, Women